2012
DOI: 10.3390/molecules170911216
|View full text |Cite
|
Sign up to set email alerts
|

Salvianolic Acid A Protects the Peripheral Nerve Function in Diabetic Rats through Regulation of the AMPK-PGC1α-Sirt3 Axis

Abstract: Salvianolic acid A (SalA) is one of the main efficacious, water-soluble constituents of Salvia miltiorrhiza Bunge. This study investigated the protective effects of SalA on peripheral nerve in diabetic rats. Administration of SalA (0.3, 1 and 3 mg/kg, ig) was started from the 5th week after strepotozotocin (STZ60 mg/kg) intraperitoneal injection and continued for 8 weeks. Paw withdrawal mechanical threshold (PWMT) and motor nerve conduction velocity (MNCV) were used to assess peripheral nerve function. The wes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
34
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 31 publications
5
34
0
Order By: Relevance
“…It was found that application of AICAR could activate AMPK, as well as decreasing oxidative stress and decreasing nociceptive response in diabetic rats. In addition, metformin and AICAR could not only activate AMPK, but also regulate the expression of AMPK target gents (PGC-1α, Sirt3 and nNOS), which has been shown to be to be involved in diabetic neuropathy (Yu et al, 2012). All those findings confirmed the involvement of AMPK activation in the decrease of oxidative stress and nociceptive response in diabetic rats.…”
Section: Discussionmentioning
confidence: 61%
“…It was found that application of AICAR could activate AMPK, as well as decreasing oxidative stress and decreasing nociceptive response in diabetic rats. In addition, metformin and AICAR could not only activate AMPK, but also regulate the expression of AMPK target gents (PGC-1α, Sirt3 and nNOS), which has been shown to be to be involved in diabetic neuropathy (Yu et al, 2012). All those findings confirmed the involvement of AMPK activation in the decrease of oxidative stress and nociceptive response in diabetic rats.…”
Section: Discussionmentioning
confidence: 61%
“…A recent study reports that regulation of the AMPK- PGC-1α- sirtuin 3 axis protects peripheral nerve function in the diabetic rat (Yu et al, 2012). However, the current study presents novel evidence that loss of PGC-1α can directly cause neuropathy that is worsened by diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…We have summarized a few of new approaches in Table 2 [7997]. Hopefully, some reviews in the recent years have proven positive effects of natural antioxidants and herbal products such as Satureja species and Urtica dioica in diabetes and its complications [111116].…”
Section: New Therapeutic Approaches For Dnmentioning
confidence: 99%